From mechanisms to management: a comprehensive review of sarcopenia in gastric cancer - Liu, Wenhao; Cao, Hongliang; Zhou, Xuanpeng; Sun, Luanbiao; Li, Linchun; Song, Xinyuan; Gao, Yang; Xing, Jianpeng; Gao, Shuohui (Frontiers in Nutrition, 2026)
Gastric cancer (GC), a leading cause of global cancer mortality, induces systemic changes impacting patient prognosis. A growing body of evidence shows a significantly increased prevalence of sarcopenia in GC patients, closely linked to poor outcomes such as higher postoperative complications, enhanced chemotherapy toxicity, and shortened survival. However, its underlying mechanisms and optimal management remain not fully clarified. This review comprehensively analyzes the pathological mechanisms and clinical significance of GC-related sarcopenia, emphasizing systemic inflammation, metabolic/nutritional disorders, neuroendocrine dysfunction, and anti-tumor therapy impacts. Additionally, feasible management methods such as nutritional support, exercise intervention, and related drug treatment were also proposed. By synthesizing current evidence, we delineate sarcopenia’s integral role in GC and propose pragmatic strategies to ultimately improve patient outcomes.